인구기반 표준 코호트를 이용한 대장 내시경 후 천공 발생: 후향적, 환자-대조군 연구 - 김지우; Ji Woo Kim; 김수영; Su Young Kim; 최정혜; Jung Hye Choi; 김현수; Hyun-soo Kim; 이정국; Jung Kuk Lee; 김윤태; Yun Tae Kim; et al. (The Korean journal of gastroenterology, 2019)
Background/Aims: Despite the many reports of colonoscopy complications worldwide, few studies have been performed at the population level in Korea. In this study, a population-based study was performed to evaluate the incidence of post-colonoscopy perforations compared to a control group. Methods: Between January 2011 and December 2011, data for all cases (age over 45) who underwent a colonoscopy were collected from National Health Insurance Service using a random sampling method. The clinical characteristics and perforation incidence (within 30 days after the colonoscopy) of cases were identified, and cases were then compared with controls who had not undergone a colonoscopy. Results: Among 1,380,000 subjects, 31,177 cases and 62,354 controls were identified. Perforation occurred in 14 patients (0.04%) in the case group and one patient (<0.01%) in the control group (RR, 28.0; 95% CI 3.7-212.9, p<0.001). Subgroup analysis was followed according to the endoscopic procedure, gender and age. In subgroup analysis, colonoscopy-associated perforations occurred more in the therapeutic procedure (RR, 26; 95% CI 1.46-461.46), male (RR, 50; 95% CI 2.96-844.41), and age of 45-60 years (RR, 30; 95% CI 1.71-525.23). Conclusions: A colonoscopy procedure is related to an increased risk of perforation at the population level. In addition, the therapeutic procedure, male, and